1998
DOI: 10.1046/j.1440-1703.1998.00266.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial pattern changes in aboveground plant biomass in a grazing pasture

Abstract: Using gamma distribution and spatial autocorrelation, it was demonstrated that plant biomass per unit area of a pasture grazed by cattle exhibited two kinds of spatial heterogeneity: small‐scale heterogeneity caused by grazing and large‐scale heterogeneity caused by topography, land aspect, etc. For each of the 10 measurement times from May to August, 100 quadrats 50 cm × 50 cm were arranged along a straight line 50 m long in a pasture, and the plants within the quadrats were harvested at the height of 3 cm ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 13 publications
3
35
2
Order By: Relevance
“…11). This conflicts with the observations made by Shiyomi et al (1983b) on sheep, who found that heterogeneity increased as a result of grazing (as observed in the RR, RS and NS strategies in this study). This may indicate that the sheep in Shiyomi et al's (1983b) study used a strategy similar to NS, which produces good results at low stocking density (Fig.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…11). This conflicts with the observations made by Shiyomi et al (1983b) on sheep, who found that heterogeneity increased as a result of grazing (as observed in the RR, RS and NS strategies in this study). This may indicate that the sheep in Shiyomi et al's (1983b) study used a strategy similar to NS, which produces good results at low stocking density (Fig.…”
Section: Resultscontrasting
confidence: 99%
“…The results given in Shiyomi et al (1983b) indicate that both the mean µ and the parameterp decrease with time over a day's grazing. This implies that the field becomes "patchier", or more heterogeneous, under grazing.…”
Section: Creation Of Heterogeneitymentioning
confidence: 88%
See 3 more Smart Citations